Parents' experiences of being involved in medical decision-making for their child with a life-limiting condition: A systematic review with narrative synthesis - Polakova, Kristyna; Ahmed, Faraz; Vlckova, Karolina; Brearley, Sarah G (Palliative medicine, 2024)
BACKGROUND: Parental involvement in the decision-making processes about medical treatment for children with life-limiting conditions is recognised as good practice. Previous research highlighted factors affecting the decision-making process, but little is known about how parents experience their participation. AIM: To explore how parents experience their participation in the process of decision-making about treatment and future care for their children with life-limiting conditions. DESIGN: A systematically constructed review using narrative synthesis. The PRISMA guidelines were followed to report the findings. Databases Medline, EMBASE, SCOPUS, CINAHL and PsycINFO were searched up to December 2023. The study protocol was registered at PROSPERO (RN CRD42021215863). RESULTS: From the initial 2512 citations identified, 28 papers met the inclusion criteria and were included in the review. A wide range of medical decisions was identified; stopping general or life-sustaining treatment was most frequent. Narrative synthesis revealed six themes: (1) Temporal aspects affecting the experience with decision-making; (2) Losing control of the situation; (3) Transferring the power to decide to doctors; (4) To be a 'good' parent and protect the child; (5) The emotional state of parents and (6) Sources of support to alleviate the parental experience. CONCLUSIONS: Parental experiences with decision-making are complex and multifactorial. Parents' ability to effectively participate in the process is limited, as they are not empowered to do so and the circumstances in which the decisions are taking place are challenging. Healthcare professionals need to support parental involvement in an effective way instead of just formally asking them to participate.
Keywords: klinické rozhodování; Child; Narration; Decision Making; rodiče; Health Personnel; rozhodování; Humans; vyprávění; Clinical Decision-Making; lidé; zdravotnický personál; Parents; dítě